A Tool Detects Violation Of Road Markings Using Ultrasonic Sensors Based On Internet Of Things - Yo Ceng Giap; Yohanes Manurung; Ma'mun Johari (bit-Tech, 2019)
In our daily lives, of course we often see the number of motorbike or car vehicles that do not care about the traffic lights, even though the traffic is red, but there are always vehicles that stop or even slightly cross the white line that is specifically for pedestrians so that can pass when the traffic lights are red. Ultrasonic sensors work based on the principle of reflection of sound waves, where these sensors produce sound waves which then capture it again with a time difference as the basis for sensing. After analyzing the needs, the author will build a Tool to Detect Road Marking Violations Using the Internet-Based Ultrasonic Sensor on the grounds that all the components needed in building the tool already exist. Which is where the driver will be exposed to a photo if it crosses the marking line that has been provided on the highway. Because the concept of the internet of things involves tools with users to communicate. The composition of the algorithm, the author uses python which has become the default programming language raspbian operating system. Algortihm construction in the tool is a red light algorithm, an ultrasonic sensor algorithm, an image capture algorithm, and an algorithm for sending text and images via email. Traffic officers will be facilitated because the tool is in accordance with the traffic light seconds, can take pictures, and also officers are informed in the form of text and images.